Effeciency using of land resources: economical and analytical aspect - Петренко, Ж. А.; Томашевська, О. А. (Scientific Progress & Innovations, 2012)
The factors of increase of efficiency of using of the land holdings of region are reflected in the context of their value in search of reserves and directions of growth of economy of agrarian enterprises. The deep quantitative statistic and economical analysis of effective synthetic economic performance indicators is carried out through the prism of factors, predetermining the level of their return in indexes arrived from the hectare of area. The quantitative measure of influence on profitability of the indicated unit of area of such factors as: quality of the land holdings; intensity of financial and labour investments; supply with land workers of these enterprises; supply with fund productions.